Influence of Welding Process on Microstructure and Properties of Laser Welding of SiCp/6061 Al Matrix Composite - Li, Hongliang; Cao, Hongyang; Zhu, Qiang; Lu, Yunbin; Wang, Zeyu; Zhao, Wentao; Xia, Hongbo (Frontiers in Materials, 2021)
Direct laser welding, laser welding with Ti interlayer, and ultrasonic-assisted laser welding with Ti interlayer were used to join SiCp/6061 Al matrix composites. Microstructural evolutions, compositional distributions and tensile strengths under three processes were compared and analyzed. The experimental results showed that ultrasonic-assisted laser welding with Ti interlayer can obtain joints with good continuity and without obvious defects. Due to combined effects of Ti interlayer and ultrasonic, formation of brittle Al4C3 phase was greatly suppressed and fine TiC precipitates were also uniformly distributed in weld metal. The strength of welded joints could reach up to 77.2% of the base material. Because of the internal defects (voids and pores) in weld metal and the generated large numbers of brittle phases of Al4C3, the joint strength of the direct laser welding and laser welding with Ti interlayer can only reach 49.4% and 64.8% of the base material strength, respectively.